Potentially Inappropriate Medication Use Among Older Adults with Cognitive Impairment and Dementia Attending Primary Care-Based Memory Clinics - Rishabh Sharma; Linda Lee; Feng Chang; Tejal Patel (Pharmacy)
Potentially inappropriate medications (PIMs) increase the risk of adverse drug reactions, hospitalizations, and worsened health outcomes in older adults, particularly those with cognitive impairment (CI) or dementia. This study was designed to compare the Beers Criteria® 2023 and the Screening Tool of Older Persons’ Potentially Inappropriate Prescriptions (STOPP) Criteria 2023 to determine which identifies a higher prevalence of PIMs in older adults with CI or dementia attending primary care-based memory clinics. PIMs were identified with the use of the updated Beers Criteria® 2023 and STOPP Criteria 2023, from electronic medical records of study participants from January to August 2023. The study identified PIMs and analyzed associated risk factors using bivariate logistic regression. Of 44 older adults, 47.7% (n = 21) were detected with one PIM based on Beers Criteria® 2023, and 27.2% (n = 12) were identified with at least one PIM using STOPP criteria. Using the updated Beers Criteria® 2023 and STOPP Criteria 2023, the study identified 50 PIMs (averaging 0.9 PIMs per participant) based on Beers Criteria® and 31 PIMs (averaging 0.6 PIMs per participant) based on STOPP Criteria, respectively. Bivariate logistic regression revealed a significant association between having nine or more comorbidities and PIMs according to Beers Criteria® (odds ratio (OR) = 8.4, 95% confidence interval (CIn) = 1.27–55.39, p = 0.027). This study highlights the high prevalence of PIMs among older adults with CI or dementia, emphasizing the need for regular medication reviews. Implementing both criteria can enhance medication management and improve patient safety in this vulnerable population.